PERSEPSI PENGUNJUNG KAMPUNG KEREN TERHADAP KEGIATAN KOMUNIKASI PEMASARAN PEMKOT KEDIRI DALAM MEMPROMOSIKAN KAMPUNG KEREN - Mahadewi, Kellina (INFOKOM (Informatika & Komputer), 2023)
ABSTRACT Background: The concept of downtown tourism is currently being developed by the Kediri City Government to enlighten the surrounding community, named Creative and Independent Village (Kampung Keren) program since 2021. This topic is interesting for research because the determination of Kampung Keren was not accompanied by an effective communication program. The government does not provide special media that fully exposes Kampung Keren. The lack of marketing communication activities can certainly affect visitors’ perceptions of Kampung Keren. Purpose: This study was structured to describe visitors’ perceptions of Kampung Keren towards marketing communication activities carried out by the Local Government in promoting Kampung Keren. The theory used also discusses marketing communications and perceptions. Method: The method used in this study is qualitative with a descriptive type, while data collection techniques are carried out by observation, in-depth interviews, and literature studies. Results: Based on the results of this study, visitors only know about marketing communication activities through the IG Kediri City Government and the website only. Visitors also gave good responses to the activities carried out, although there were still informants who assessed that marketing communication activities were still lacking and needed improvement. Conclusion: Based on information that has been uploaded, it is possible for the public’s perception of Kampung Keren’s marketing communications to have a positive value. Keywords: perception, marketing communications, visitors, Kampung Keren.